Perspectives of clinicians on shared decision making in hospice care for advanced cancer patients in Nanjing: a descriptive qualitative study - Tianyu Pang; Kairan Yan; Yujie Zhou; Lulu Sun; Ligui Wu; Ling Yuan; Zhi Zhou (BMC Palliative Care)
Abstract Background As the cancer burden increases in China, the need for hospice care is escalating. The right of informed consent to hospice care for patients with advanced cancer is still at the experimental stage, and patients still face numerous obstacles when it comes to participating in hospice care decision-making. In this context, we conducted a qualitative study to explore perspectives of clinicians on shared decision making (SDM) in hospice care for advanced cancer patients. Methods This study employed a descriptive phenomenological research method. We conducted semi-structured interviews with clinicians recruited from 4 hospital in Nanjing, Jiangsu Province, China from January to March 2023. Two researchers used Colaizzi 7-step analysis method to analyze, summarize, integrate and refine the data. Results A total of 17 clinicians participated. Three main themes were extracted: (1) Clinician attitudes regarding SDM; (2) Influencing factors are multidimensional; (3) Recommendations for implementing SDM in hospice care decision-making. Conclusion SDM in hospice care for advanced cancer patients was affected by multiple factors in medical practice. It is highly desirable to focus on improving the decision support system, optimizing the SDM model of hospice care to ensure the informed choice of patients with advanced cancer.